A small plot study of Chalara infestation in a recently established natural stand of ash, UK. Issue 3 (2nd July 2016) - Hobson, Peter R.; Ibisch, Pierre L.; Parmee, Richard
Abstract : A small plot study of Chalara infestation was carried out in a recently established stand of natural secondary woodland on an abandoned field in Suffolk. The aim was to determine the pattern of disease spread in relation to the structure of young ash stands. Wind-dispersed colonisation by ash was typically patchy but clustered along the eastern edge of mature ancient semi-natural woodland. All the trees were small with an average diameter of 1.25 ± .614 cm and average height of 1.63 ± 1.54 metres. Symptoms of dieback were recorded in 51% of the 220 quadrats surveyed but was most prevalent in areas where tree density was highest. Of the 1, 343 trees sampled 33% were infected and showing advanced stages of dieback in areas where the disease was most concentrated. The observed positive correlation between tree height and the prevalence of dieback may be due to chance effects emerging from larger patterns of wind-born dispersal in both host and pathogen. The results of the study point to indiscriminate modes of infection operating at local levels and determined by the presence of high numbers of host trees. High levels of infection in early stages of growth suggests ash has little chance to establish itself before it is culled by the disease. The findings also highlight the vulnerability of homogenous stands to wind-borne pathogens.